An admission control method to provide higher sampling rates over space launchers networks. Issue 24 (2019) - Petit, Dorine; Georges, Jean-Philippe; Divoux, Thierry; Regnier, Bruno; Miramont, Philippe
Abstract: Nowadays, embedded network systems, like in space launcher application, trends to move from a bus communication to components off-the-shelf (COTS) such as Ethernet switched network in order to reduce the cost and the mass. In order to guaranty the real time and reliability constraints on an Ethernet switched network which is not deterministic, the network is oversized and redundant. In this way, lot of resources are not used. This paper focus on using these available resources to support higher sampling rates for better controllability, safety and freshness. A framework for rate admission control is defined and an algorithm is proposed to maximise the sampling rate (i.e. the throughput) of each flow while satisfying maximum end-to-end delays requirements. The purpose of using this algorithm has been brought to light through an experiment based on the next generation of space launcher network.